(‐)‐Hydroxycitric Acid Nourishes Protein Synthesis via Altering Metabolic Directions of Amino Acids in Male Rats. (4th May 2016) - Han, Ningning; Li, Longlong; Peng, Mengling; Ma, Haitian
Abstract : (‐)‐Hydroxycitric acid (HCA), a major active ingredient of Garcinia Cambogia extracts, had shown to suppress body weight gain and fat accumulation in animals and humans. While, the underlying mechanism of (‐)‐HCA has not fully understood. Thus, this study was aimed to investigate the effects of long‐term supplement with (‐)‐HCA on body weight gain and variances of amino acid content in rats. Results showed that (‐)‐HCA treatment reduced body weight gain and increased feed conversion ratio in rats. The content of hepatic glycogen, muscle glycogen, and serum T4, T3, insulin, and Leptin were increased in (‐)‐HCA treatment groups. Protein content in liver and muscle were significantly increased in (‐)‐HCA treatment groups. Amino acid profile analysis indicated that most of amino acid contents in serum and liver, especially aromatic amino acid and branched amino acid, were higher in (‐)‐HCA treatment groups. However, most of the amino acid contents in muscle, especially aromatic amino acid and branched amino acid, were reduced in (‐)‐HCA treatment groups. These results indicated that (‐)‐HCA treatment could reduce body weight gain through promoting energy expenditure via regulation of thyroid hormone levels. In addition, (‐)‐HCA treatment could promote protein synthesis by altering the metabolic directions of amino acids. Copyright © 2016 John Wiley & Sons, Ltd.